Need and Organizational Aspects of Human Audit in Modern Enterprises and Organizations - Bakieva I.A; Raxmatullaeva Sh.X (Zien Journals, 2022)
This article is based on the current aspects and necessity of personnel audit in enterprises and organizations. The essence of the audit of personnel is theoretically described, and the organizational aspects of its conduct are divided into levels, the object, directions and requirements for this process.
Keywords: Audit; personnel audit; personnel assessment; conduct